Spastic Diplegic and Tetraplegic Cerebral Palsy Compared - J Gordon Millichap (Pediatric Neurology Briefs)
Risk factors of cerebral palsy (CP), seizures, CP severity, EEG, and MRI findings were compared in 38 children with spastic diplegic (DCP) and 48 with spastic tetraplegic (TCP), in a report from Medical University of Bialystok, Poland.